Isolation, Characterization, In-silico and enzyme Inhibition studies of plant Bougainvillea spectabilis against a hyperoxaluria Initiator Glycolate oxidase (International Journal of Pharmaceutical Sciences and Drug Research, 2023)
Glycolate oxidase has long been thought to be a key player in the formation of oxalate accumulation in the human body. Both the endogenous synthesis of oxalate and clinically identified targets for the therapy of primary hyperoxaluria are affected by this disorder. The role of glycolate oxidase has been investigated in order to provide additional insight into the possible molecular pathways involved. The presence of flavonoids in the ethanolic extract led to the conclusion that it was suitable following phytochemical screening. Column chromatography was used to isolate the active component using the proper solvent system. The structure of the active, separated phytoconstituents was ascertained using a variety of spectral techniques, including FTIR, NMR, and GCMS analysis. Following structure elucidation, glycolate oxidase (PDB: 2RDT) and Quercetin were used as standards in molecular docking investigations. Studies on in- vitro enzyme inhibition were carried out to verify the outcome. Following the investigation of the isolated compound's spectral data, it was determined that the structure might be 4-hydroxy-3-nitro coumarin. Using conventional standard flavonoid Quercetin, additional molecular docking studies were carried out to speculate on the compound's potential mechanism of action. The chemical was discovered to be effective during the inhibition of the target enzyme by occupying the majority of the amino acid active sites. In-vitro enzyme inhibition tests provided additional confirmation for the computational investigations. The isolated compound's significant IC50 value in this study was demonstrated in comparison to standard Quercetin's efficacy. These findings supported the isolated compound's potential mechanism of action, which involves inhibiting the enzyme glycolate oxidase, in terms of its anti-urolithiasis efficacy. The study also provided justification for the compound's potential therapeutic application in urolithiasis.